WORKING TIME, PRODUCTIVITY, AND COSTS OF MANUAL WOOD EXTRACTION IN PRIVATE FORESTS - budiaman, ahmad; Hardjanto; Lively Limbong, Zest (Jurnal Belantara, 2025)
Wood extraction using human power is a popular wood extraction technique in private forest harvesting in Indonesia. The method is used for transporting short logs over a short distance in flat or steep areas, which do not have adequate transport roads. The study aimed to analyze time consumption, productivity, and costs of wood extraction using human power in private forests. The study was conducted in a private forest in Probolinggo, East Java. The study was carried out in two cutting blocks. The first cutting block was 50 m from the landing, while the second was 250 m. The data collected included working time, productivity, and costs of wood extraction using human power. Working time data were obtained through video analysis, diameter, and tree height data were collected through direct measurements in the field, and cost data was obtained through direct measurements and interviews. Work time analysis was carried out for 73 cycles for cutting block 1 and 57 cycles for cutting block 2. The results showed that the workers spent most of their time on loaded trips, followed by empty travel, and for personal purposes. The lowest working time was placing and arranging the wood at the landing. The average wood extraction time per cycle was 4.49 minutes for a skidding distance of 50 m and 16.30 minutes for a skidding distance of 250 m. The results showed that the productivity of wood extraction using human power varied from 0.45 to 1.75 m3/hour. The cost of wood extraction using human power in private forests was IDR. 13.33/m3 for a skid distance of 50 m and IDR 51.85/m3 for a skidding distance of 250 m